IMPLEMENTASI MODUL AJAR BERBASIS LITERASI DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KECERDASAN BUDAYA PADA SISWA KELAS X SMA - Arianto, Arianto; Sastromiharjo, Andoyo; Nissa, Barkatun; Bujaya, Muhammad; Kustina, Rika; Talitha, Stella; Trisnawati, Trisnawati; Nina, Nina (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the effect of implementing a literacy-based teaching module on improving critical thinking skills and cultural intelligence of Grade X students at Al-Amanah Islamic School, Lembang, West Java. This research employed a quantitative approach with a one-group pre-test and post-test experimental design. Data were collected using essay tests (to assess critical thinking) and Likert-scale questionnaires (to measure cultural intelligence). Statistical test results showed a significant difference between pre-test and post-test scores on both variables. The paired samples t-test revealed a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating that the implementation of the literacy-based teaching module significantly enhanced students’ critical thinking and cultural intelligence. These findings highlight the importance of developing teaching materials that integrate local cultural values and literacy strategies to strengthen student competencies in the face of educational globalization.